Analisis Yuridis Masa Jabatan Ketua Umum Partai Politik dalam Negara Demokrasi Perspektif Siyasah Dusturiyah - Kaka Anugrah Miranto; Khalid (Bahasa Indonesia, 2026)
Political parties play a strategic role in Indonesia's democratic system as a means of public political participation and political recruitment for public office. However, Law Number 2 of 2011 on Political Parties does not specifically regulate the periodicity and term of office of the chairperson of political parties. Article 23 paragraph (1) delegates the change of management to the Statutes and Bylaws of each party. This situation creates inconsistencies in regulations and opens the door for someone to hold the position of general chairman for more than two terms. This research uses a juridical-normative method with a juridical-constitutional and siyasah dusturiyah approach. The research aims to analyze the implications of the absence of term limits and to find the ideal concept of term limits for political party chairpersons. The analysis results show that limitations are necessary to maintain regeneration, internal democracy, accountability, and to prevent personalization and concentration of power. In the perspective of siyasah dusturiyah, these restrictions align with the principles of justice (al-'adl), accountability (al-mas'uliyyah), public interest (mashlahah 'ammah), consultation, and the trust of leadership.